Challenges in extracting a defective ventricular lead after CRT-D: a case report - Özmen, Murat; Aydınyılmaz, Faruk (Frontiers in Cardiovascular Medicine, 2025)
BackgroundOur aim in this case was to remove the defective ventricular lead and the ruptured coronary sinus lead.MethodsEntering through the right femoral vein and removing the coronary sinus lead with a pigtail catheter.ResultsIn our attempt to extract the coronary sinus lead, it fractured. The broken fragment was successfully removed without any complications.ConclusionsIn this case, which is very rarely encountered in daily practice, we successfully removed the coronary sinus lead from the body from the femoral vein using a pigtail catheter with a new method.